Enhancing Sharia Assets Among the Youth Through Financial Intelligence - Akbar, Andi Heriasdiva; Razak, Syaparuddin; Hasbi, Hartas (Institut Keuangan-Perbankan Dan Informatika Asia Perbanas, 2024)
This study aims to explore the significant role of Theory Planned Behavior and financial intelligenceamong the youth, especially the Millenial generationin shaping Sharia-compliant investment behavior. A quantitative descriptive research method was employed, collecting data through questionnaires from two hundredrandomly selected respondents between June and August 2023. The findings indicate that perceived behavioral control and financial intelligence significantly influence Sharia-compliant investment decisions. The research findings confirm that financial intelligence significantly influences Sharia-compliant investments in asset development. Additionally, perceived behavioral control significantly affects Sharia-compliant investments in asset development. Furthermore, the complex interaction between Sharia financial literacy, attitude, subjective norms, and perceived behavioral control significantly contributes to financial intelligence. This confirms that Sharia financial literacy significantly influences financial intelligence, attitude significantly influences financial intelligence, subjective norms significantly influence financial intelligence, and perceived behavioral control significantly influences financial intelligence. These findings emphasize the importance of Sharia financial literacy and understanding Sharia principles in effectively managing investments. Financial literacy, positive attitudes, and subjective norms play crucial roles in enhancing individuals' financial intelligence, supporting Sharia-compliant investment decisions. Millennials need to enhance their financial literacy and intelligence for effective Sharia-compliant investments.